Desain Bahan Ajar Matematika Berbasis Aplikasi I Mind Mapp Untuk Meningkatkan Kemampuan Pemahaman Konsep dan Ketertarikan Siswa Pada Mata Pelajaran Matematika - Uun Pertiwi; Nanang Khuzaini (CV. Multi Kreasi Media, 2022)
The purpose of this research is to increase the understanding of learning concepts and students' interest in Mathematics subject matter of Quadratic Equations. The research method uses qualitative methods with the subject of class IX students. The instrument in this study used the observation and questionnaires and tests. Observations were made to teachers and students to determine student needs, student problem skills, and understanding student learning concepts. This research has several results. First, students' learning needs are still low, students' problem-solving skills are still lacking, students' understanding of students' learning concepts in mathematics learning is still very lacking. The researcher concludes that the needs of students in the I mind map teaching materials are needed to improve students' understanding abilities